From pure compounds to complex exposure: Effects of dietary cadmium and lignans on estrogen, epidermal growth factor receptor, and mitogen activated protein kinase signaling in vivo. (24th June 2016) - Ali, Imran; Hurmerinta, Teija; Nurmi, Tarja; Berglund, Marika; Rüegg, Joelle; Poutanen, Matti; Halldin, Krister; Mäkelä, Sari; Damdimopoulou, Pauliina
Highlights: Endocrine activity of diet-bound cadmium and lignans at human relevant exposure. Diet rich in cadmium activates EGFR-MAPK signalling as predicted by CdCl2 exposure studies. Enterolactone is an estrogen modulator as pure compound but not in dietary exposure. Dietary and pure compound exposure can be compared in controlled settings in vivo . Abstract: Exposure to environmental endocrine active compounds correlates with altered susceptibility to disease in human populations. Chemical risk assessment is single compound based, although exposure often takes place as heterogeneous mixtures of man-made and natural substances within complex matrices like diet. Here we studied whether the effects of cadmium and enterolactone on endocrine endpoints in dietary exposure can be predicted based on pure compound effects. Ovariectomized estrogen reporter ERE-luciferase (ERE-luc) mice were maintained on diets that intrinsically contain increasing concentrations of cadmium and enterolactone precursors for three and 21 days. The activation of the ERE-luc, epidermal growth factor receptor (EGFR), mitogen activated protein kinase (MAPK)-ERK1/2, and classical estrogen responses were measured. Interactions between the diets and endogenous hormone were evaluated by challenging the animals with 17β-estradiol. Compared to animals on basal purified diet, mice consuming experimental diets were exposed to significantly higher levels of cadmium and enterolactone, yet the exposure remained comparable to typical human dietary intake. Surprisingly, we could not detect effects on endpoints regulated by pure enterolactone, such as ERE-luc activation. However, cadmium accumulation in the liver was accompanied with activation of EGFR and MAPK-ERK1/2 in line with our earlier CdCl2 studies. Further, attenuation of 17β-estradiol-induced ERE-luc response in liver by experimental diets was observed. Our findings indicate that the exposure context can have substantial effects on the activity of endocrine active compounds in vivo . Thus, whenever possible, a context that mimics human exposure should be tested along with pure compounds.